2017
DOI: 10.5658/wood.2017.45.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Wood Species Identification of Korean Softwood Based on Convolutional Neural Networks

Abstract: Automatic wood species identification systems have enabled fast and accurate identification of wood species outside of specialized laboratories with well-trained experts on wood species identification. Conventional automatic wood species identification systems consist of two major parts: a feature extractor and a classifier. Feature extractors require hand-engineering to obtain optimal features to quantify the content of an image. A Convolutional Neural Network (CNN), which is one of the Deep Learning methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Below is an overview of the most recent publications in this field. Kwon et al (2017) proposed six different CNN models (variants of LeNet and MiniVGGNet architetures) to identify five softwood species from Korea. A smartphone camera was used for obtaining macroscopic wood images.…”
Section: Introductionmentioning
confidence: 99%
“…Below is an overview of the most recent publications in this field. Kwon et al (2017) proposed six different CNN models (variants of LeNet and MiniVGGNet architetures) to identify five softwood species from Korea. A smartphone camera was used for obtaining macroscopic wood images.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of wood species using texture characteristics of transverse cross-section microscopic images is the focus of the current study. Some authors, such as [6,7], use the images as inputs for convolutional neural network (CNN), where the features are extracted by the classifier. Other authors explore and extract features using standard texture methods such as Local Binary Patterns (LBP) [2,8], Local Phase Quantization (LPQ) [9], gray level co-occurrence matrix [10] or Mathematical morphological operation and K-L divergence [11].…”
Section: State Of the Artsmentioning
confidence: 99%
“…This classifier can be combined with BP neural network and Mahalanobis distance (MD) to perform hardwood species classification [11]. In recent years, a deep learning classifier, such as CNN architectures, has started to be exploited [6,7,12].…”
Section: State Of the Artsmentioning
confidence: 99%
“…Recently, CNNs have been employed to classify wood species using datasets containing wood images. Kwon et al (2017) reported the possibility and performance of softwood species classification using CNN-based models, such as LeNet and miniVGGNet. Kwon et al (2019) improved the performance of automated species classification by using a CNN with ensemble methods.…”
Section: Introductionmentioning
confidence: 99%